Pattern of regional metastasis in papillary thyroid cancer: our experience of 86 cases - Das, Rajjyoti; Sharma, Jagannath D.; Kataki, Amal Ch; Kalita, Chandi R.; Baishya, Nizara (International Journal of Research in Medical Sciences, 2019)
Background: Papillary thyroid cancer (PTC) have a high propensity for regional metastasis which ranges from 30- 80%. The objective of the study is to assess the pattern of lymph node metastasis and to plan the extent of neck dissection accordingly. Though central neck dissection (CND) is routinely done in PTC but the indication of extent of neck dissection is still controversial. Methods: The medical records of 86 patients with PTC who underwent total thyroidectomy (TT) and neck dissection at Dr. B. Borooah Cancer Institute(BBCI) from January 2010 to December 2014 were retrospectively reviewed. Results: Out of 86 patients 22 were males and 64 were females. The median age of presentation was 40.0 years. 43 out of 86 patients (50%) had cervical lymph node metastasis. Ipsilateral nodal metastasis was found in 37 patients (43.0%) and contralateral metastasis was found in only 6 patients (7.0%).Tumors with size more than 3cm had ipsilateral nodal metastasis in 21(56.7%) patients which is statistically significant (p 0.03).A strong association was found between level VI and the ipsilateral group of lymph nodes involving level II,III,IV and V. Conclusions: Majority of patients present with multiple level nodal metastasis, with the central compartment commonly involved. In view of the high incidence of metastatic lymph nodes in levels II, III, IV and level VI ,our study supports the recommendation for posterolateral and anterior neck dissection in patients with clinically positive neck nodes and tumor with aggressive criteria.